Spatiotemporal pattern of wheat harvest duration and its driving factors in the Huang-Huai-Hai plain of China - Renhai Zhong; Cong Chen; Guan Zhou; Xingguo Xiong; Qiyu Tian; Jingfeng Huang; Guangqiao Cao; Tao Lin (Computers and Electronics in Agriculture, 2026)

Habitat changes induced by converting coastal aquaculture to wetlands enhance taxonomic diversity and cross-species interaction strength of macro- and meiobenthos - Jichen Qiu; Wenjing Cao; Zhaohan Zhang; Junhong Bai; Liangxing Cao; Yuhao Xu; Jiajie Mei; Yaqi Wang; Yue Liu; Jingfeng Wang; Yanan Zhang (Aquaculture, 2026)

Editor's note to “The Grain-for-Green project offsets warming-induced soil organic carbon loss and increases soil carbon stock in Chinese Loess Plateau” [Sci. Total Environ. 837 (2022), 155469] - Huiwen Li; Yiping Wu; Shuguang Liu; Wenzhi Zhao; Jingfeng Xiao; Leigh A. Winowiecki; Xiaowei Yin; Fan Wang; Bellie Sivakumar; Yue Cao; Pengcheng Sun (Science of The Total Environment, 2026)

Enhanced T-cell activation and effector functions contribute to disease resistance in Streptococcus agalactiae-resistant tilapia - Ming Geng; Jingfeng Ding; Jun Xiao; Liting Chen; Jiansong Zhang; Kang Li; Jie Cheng; Yi Cao; Jialong Yang; Xiumei Wei (Aquaculture, 2026)

Multidrug-resistant plasmid modulates ammonia oxidation efficiency in Nitrosomonas europaea through cyclic di-guanylate and acyl-homoserine lactones pathways - Jinrui Cao; Chen Zhao; Lin Bo; Xinxin He; Yuchao Liu; Shang Wang; Bin Xue; Jingfeng Wang (Bioresource Technology, 2026)

Multi-parameter input damage limit prediction for bare reinforced concrete frames using XGBoost - Chen Xiong; Yuchao Cao; Jingfeng Zheng; Linlin Xie; Liu Mei; Lixiao Li; Wujian Long (Soil Dynamics and Earthquake Engineering, 2025)

The environmental concentration of diethylstilbestrol and its structural analogues promote the conjugation transfer of ARGs through the pheromone effect - Panpan Yang; Xiaobo Yang; Feng Wang; Rumeng Li; Man Zhang; Jingxue Qian; Ruolin Hao; Zhiqiang Shen; Jingfeng Wang; Lijuan Zhang; Zhigang Qiu; Yanhua Cao (Journal of Hazardous Materials, 2025)

Unveiling uncertainties in soil organic carbon modeling: the critical role of climate response functions - Huiwen Li; Yue Cao; Jingfeng Xiao; Wenxin Zhang; Yiping Wu; Arshad Ali; Zuoqiang Yuan (Environmental Modelling & Software, 2025)

Microplastics enhance the denitrification of glycogen-accumulating organisms by regulating electronic transport in carbon-nitrogen coupling - Yuchao Liu; Jinrui Cao; Sheng Li; Xinxin He; Bin Zhang; Shang Wang; Jingfeng Wang (Journal of Hazardous Materials, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Fluoride removal from coal mining water using novel polymeric aluminum modified activated carbon prepared through mechanochemical process - Yixiang Bao; Yonghui Qi; Qiao Li; Lei Wang; Zhiguo Cao; Jie Li; Min Wu; Jun Chen; Haiqin Zhang; Qiang Guo; Binbin Jiang; Jinkui Zhong; et al. (Journal of Environmental Sciences, 2024)

Chlorite and bromate alter the conjugative transfer of antibiotic resistance genes: Co-regulation of oxidative stress and energy supply - Jinrui Cao; Bin Xue; Shuran Yang; Xiaobo Yang; Xi Zhang; Zhigang Qiu; Zhiqiang Shen; Jingfeng Wang (Journal of Hazardous Materials, 2024)

Environmental benefits and supply dynamics of electric vehicles sharing: From a systematic perspective of transportation structure and trip purposes - Shunchao Wang; Jingfeng Ma; Qi Cao; Lichao Wang (Transportation Research Part D: Transport and Environment, 2024)

The occurrence, ecological risk, and control of disinfection by-products from intensified wastewater disinfection during the COVID-19 pandemic - Bin Xue; Xuan Guo; Jinrui Cao; Shuran Yang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Science of The Total Environment, 2023)

Potato (Solanum tuberosum L.) non-specific lipid transfer protein StLTP6 promotes viral infection by inhibiting virus-induced RNA silencing - Kaijie Shang; Yang Xu; Weilin Cao; Xiaoying Xie; Yanru Zhang; Jingfeng Zhang; Hongmei Liu; Shumei Zhou; Xiaoping Zhu; Changxiang Zhu (Planta, 2022)

Monitoring and evaluation of antibiotic resistance genes in three rivers in northeast China - Chen Zhao; Chenyu Li; Xiaoming Wang; Zhuosong Cao; Chao Gao; Sicong Su; Bin Xue; Shang Wang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Environmental Science and Pollution Research, 2022)

Decipher soil organic carbon dynamics and driving forces across China using machine learning - Huiwen Li; Yiping Wu; Shuguang Liu; Jingfeng Xiao; Wenzhi Zhao; Ji Chen; Georgii Alexandrov; Yue Cao (Global Change Biology, 2022)
The dynamics of soil organic carbon (SOC) play a critical role in modulating global warming. However, the long‐term spatiotemporal changes of SOC at large scale, and the impacts of driving forces remain unclear. In this study, we investigated the dynamics of SOC in different soil layers across China through the1980s to 2010s using a machine learning approach and quantified the impacts of the key factors based on factorial simulation experiments.Our results showed that the latest (2000–2014) SOC stock in the first meter soil (SOC 100 ) was 80.68 ± 3.49 Pg C, of which 42.6% was stored in the top 20 cm, sequestrating carbon with a rate of 30.80 ± 12.37 g C m −2 yr −1 since the 1980s. Our experiments focusing on the recent two periods (2000s and 2010s) revealed that climate change exerted the largest relative contributions to SOC dynamics in both layers and warming or drying can result in SOC loss. However, the influence of climate change weakened with soil depth, while the opposite for vegetation growth. Relationships between SOC and forest canopy height further confirmed this strengthened impact of vegetation with soil depth and highlighted the carbon sink function of deep soil in mature forest. Moreover, our estimates suggested that SOC dynamics in 71% of topsoil were controlled by climate change and its coupled influence with environmental variation (CE). Meanwhile, CE and the combined influence of climate change and vegetation growth dominated the SOC dynamics in 82.05% of the first meter soil. Additionally, the national cropland topsoil organic carbon increased with a rate of 23.6 ± 7.6 g C m −2 yr −1 since the 1980s, and the widely applied nitrogenous fertilizer was a key stimulus. Overall, our study extended the knowledge about the dynamics of SOC and deepened our understanding about the impacts of the primary factors.

Characterization of a novel Vibrio parahaemolyticus host-phage pair and antibacterial effect against the host - Chao Gao; Xiaobo Yang; Chen Zhao; Chenyu Li; Shang Wang; Xi Zhang; Bin Xue; Zhuosong Cao; Hongrui Zhou; Yutong Yang; Zhiqiang Shen; Pingfeng Yu; et al. (Archives of Virology, 2022)

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Condition dependence of advertisement calls in male African clawed frogs - Xiaocui Wang; Zhi-Jun Zhao; Yan Cao; Jianguo Cui; Yezhong Tang; Jingfeng Chen (Journal of Ethology, 2019)

Tissue distribution of olive flounder VDAC2 and its expression in fish cell lines - Aijun Lü; Xiucai Hu; Li Li; Chao Pei; Chao Zhang; Xianglin Cao; Xianghui Kong; Guoxing Nie; Xuejun Li; Jingfeng Sun (Fish Physiology and Biochemistry, 2015)

Trophic states of creeks and their relationship to changes in water level in Xixi National Wetland Park, China - Yufeng Li; Hongyu Liu; Jingfeng Hao; Nan Zheng; Xiao Cao (Environmental Monitoring and Assessment, 2012)

Development and evaluation of a new detection tool—visual DNA microarray for simultaneous and specific detection of human immunodeficiency virus type-1 and hepatitis C virus - Jingfeng Tang; Li Zhou; Lian Lian Duan; Yang Feng; Xuan Cao; Yefu Wang (Molecular Biology Reports, 2011)